The Effect of Participative Leadership Style and Workload on Employee Satisfaction in the Hospital - Wiliyanarti, Pipit Festi; Fahrudda, Ansarul; Rahmawati, Nur (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2025)
Employee job satisfaction is a crucial aspect in the health sector, which directly impacts the quality of patient care. In hospitals, job satisfaction is often affected by key factors such as leadership style and workload. According to data from the Central Statistics Agency of 2021, job satisfaction in the health sector is lower than in other sectors, with only 65% employees expressing satisfaction with their work. This study aims to analyze the effect of participative leadership style and workload on employee job satisfaction in the outpatient unit of Gresik Petrokimia Hospital. This current research employed a quantitative method with a cross-sectional design. Data were collected using a questionnaire distributed to 41 respondents, and then analyzed using multivariate multiple linear regression with SPSS version 25. The findings revealed that the participative leadership style had no significant effect on job satisfaction. However, workload partially had a significant effect. When assessed together, both participative leadership style and workload demonstrate a statistically significant influence on job satisfaction.